2015
DOI: 10.1371/journal.pone.0125388
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Training Prevents the Onset of Endothelial Dysfunction via Increased Nitric Oxide Bioavailability and Reduced Reactive Oxygen Species in an Experimental Model of Menopause

Abstract: ObjectivePrevious studies have shown that estrogen deficiency, arising in postmenopause, promotes endothelial dysfunction. This study evaluated the effects of aerobic exercise training on endothelial dependent vasodilation of aorta in ovariectomized rats, specifically investigating the role of nitric oxide (NO) and reactive oxygen species (ROS).MethodsFemale Wistar rats ovariectomized (OVX – n=20) or with intact ovary (SHAM – n=20) remained sedentary (OVX and SHAM) or performed aerobic exercise training on a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 47 publications
(66 reference statements)
7
19
0
3
Order By: Relevance
“…It is well known that regular aerobic exercise improves the quality of life of patients with CF through increasing expectoration of the sputum and ameliorating the decline in lung function (29,35). Exercise also enhances NO bioavailability (3,4,9). In the present study a positive correlation between the PORH-to-LTH ratio and exercise capacity suggests that a greater exercise capacity positively impacts microvascular function in CF.…”
Section: Microvascular Function and Disease Severity: Clinical Relevancesupporting
confidence: 56%
“…It is well known that regular aerobic exercise improves the quality of life of patients with CF through increasing expectoration of the sputum and ameliorating the decline in lung function (29,35). Exercise also enhances NO bioavailability (3,4,9). In the present study a positive correlation between the PORH-to-LTH ratio and exercise capacity suggests that a greater exercise capacity positively impacts microvascular function in CF.…”
Section: Microvascular Function and Disease Severity: Clinical Relevancesupporting
confidence: 56%
“…Thus, one possibility is that exercise training leads to signaling through the ERRα pathway in recent post‐menopausal women, whereas this function may be lost if training is initiated several years after menopause. This timing hypothesis does also fit with animal experiments showing beneficial effects of exercise training on vascular function in ovariectomized rats studied within 1 week of surgery . As proposed in Figure , the high estrogen levels in pre‐menopausal women may suppress the ERRα pathway.…”
Section: Introductionsupporting
confidence: 73%
“…Not all studies have, however, shown that estrogen supplementation is required for beneficial effects of exercise training on vascular function. Several studies on rodents, in which vascular function has been assessed in isolated arteries, have demonstrated that exercise training is effective in female ovariectomized rodents . Moreover, 2 recent studies on late pre‐menopausal and early post‐menopausal women, who were on average 3 years within the menopausal transition, have shown that exercise training induces similar, and, for some variables, even better effects on vascular function and markers of vascular function in post‐menopausal compared to pre‐menopausal women .…”
Section: Introductionmentioning
confidence: 99%
“…Some of the major mechanisms involved increased SIRT1, mitochondrial biogenesis, protection against oxidative stress and increased nitric oxide, all known to be involved in improved exercise performance. All of these mechanisms have been found to mediate enhanced exercise performance with chronic exercise training [2, 4, 8, 1012, 29, 31, 32, 36]. …”
Section: Discussionmentioning
confidence: 99%